China's emerging commercial space industry: Current developments, legislative challenges, and regulatory solutions. (January 2023) - Zhang, Max; Yang, Xiaonan
Abstract: With commercial participants now undertaking an ever-expanding role within the development and supply-chains of China's space industry post Document No. 60, the resulting legal challenges relating to this emerging industry status-quo has garnered much academic discussion. Specifically, while China's space industry has grown at a rapid pace within the past few decades, China's legislative framework has remained largely silent over matters relating to space. Instead, China continues to remain as the only major space-faring nation without a national space law and regime. This substantive legislative gap over China's space related activities has negatively impacted the industry's current deregulation process. While it has been the academic community's primary solution to address the industry's current substantive legislative gap through coordinated rulemaking activities, this paper aims to advance the current academic discussion by taking an alternative approach and arguing that the fundamental legislative challenge and solution to China's emerging commercial space industry, is not substantive, but rather procedural by nature. Importantly, by reconceptualizing the industry's substantive gap from one that is determined by the number of missing legal instruments, to one determined by the rate of legislative activity i.e., the pace of law-making activities vis-à-vis commercial expansion, this paper argues that only through the implementation of legal procedural rulemaking mechanisms will China's space law regime be able to sufficiently address the current substantive legislative gap at a pace matching commercial expansion. Highlights: The deregulation of China's space industry. Regulatory structure and legal challenges of China's space industry. A procedural argument to resolve China's substantive space law gap.